Cellular and humoral responses in the respiratory tract of goats following intranasal stimulation using formalin-killed Pasteurella haemolytica A2 - Zamri-Saad, M.; Effendy, A.W.M.; Israf, D.A.; Azmi, M.L. (Elsevier Science B.V., 1999)
A study to determine the immunoglobulin and cellular responses in the respiratory tract of goats following intranasal exposures to formalin-killed Pasteurella haemolytica A2 was carried out. Forty-two goats were divided into two groups. Goats in Group 1 were subjected to double intranasal exposures to formalin-killed P. haemolytica A2 while goats in Group 2 were the unexposed control. Prior to and at weekly intervals post-exposure, three goats from each group were killed, serum samples were collected while the lungs were flushed with 50ml normal saline before the right apical lobes were fixed in 10% buffered formalin. Both serum and lung lavage fluid were subjected to enzyme-linked immunosorbent assay (ELISA) to determine the levels of IgA, IgM and IgG while the formalin-fixed tissues were examined histologically. IgA levels in the lung lavage fluid increased rapidly to reach a significantly (p<0.05) high level as early as Week 2 post-exposure and remained significantly (p<0.05) high throughout the study period. The IgM levels increased at an intermediate rate to reach a significantly (p<0.05) high level at Week 3 post-exposure before they decreased to an insignificant (p>0.05) level the following week and the weeks thereafter. IgG levels increased gradually and only reached a significantly (p<0.01) high level at Weeks 5 and 6 of the study. The size of the bronchus-associated lymphoid tissue (BALT) and the number of lymphocytes in BALT increased significantly from Week 2 and remained high thereafter. However, differences in the numbers of BALT were insignificant (p>0.05) initially before becoming significantly (p<0.05) high at Weeks 5 and 6. The BALT responses were parallel to those of immunoglobulins in the lung lavage fluid.